Dejavniki strateškega odločanja v podjetjih - Berginc, Dario (Teorija in praksa, 2017)
Managers have a key influence on firm performance. There is a need for a deeper understanding of their strategic decision-making. Qualitative empirical research on a sample of 17 managers showed that their strategic decision-making process is composed of gathering information, analysis information, and realisation of the decision. Key information is gathered through customer and sales data. Managers highlighted the greater confidence they have in their own information sources relative to foreign sources. They emphasised the importance of employee engagement in decision-making and the unity of management after a decision has been made. Strategic tools can support managers in their decision-making process, but they can be misleading as well. Decision-making is dominated by rational analysis, but intuitive judgment is an important complement to it.
Keywords: Decision making; Kvalitativna analiza; Managerji; Managers; Odločanje; Qualitative analysis; strateško poslovanje